Pengembangan Dashboard Data untuk Optimalisasi Layanan dan Literasi Perpustakaan di SD Negeri 2 Berkoh - Trihastuti Yuniati; Amalia Beladinna Arifa; Shintia Dwi Alika; Atika Ratna Dewi; Habibah Ratna Fadhila Islami Hana; Vania Noverina; Aprianti Ika Larasati (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
The development of library management constitutes a crucial aspect in enhancing the quality of education and fostering community literacy. School libraries fulfill a fundamental role as vital learning resource centers; however, numerous institutions continue to encounter significant challenges in operational data management and the effective utilization of technology. This community service initiative aimed to develop and implement a "Dashboard Cerdas"(or Smart Dashboard) to optimize library services at SD Negeri 2 Berkoh. The methodology employed encompassed initial observation, comprehensive data collection pertaining to book characteristics and visitor patterns, the iterative development of the interactive data visualization-based "Dashboard Cerdas", and a subsequent questionnaire-based evaluation. Findings from the field implementation indicate the successful deployment of the "Dashboard Cerdas", which has significantly facilitated systematic and transparent data management. Respondents, comprising library managers and a representative teacher, expressed high levels of satisfaction regarding the improved ease of management and the “Dashboard Cerdas” demonstrated potential in enhancing service effectiveness and stimulating student reading interest. The implications of this system are substantial, it not only augments library operational efficiency and the digital literacy of the staff but also contributes meaningfully to efforts aimed at elevating student literacy through the provision of improved, data-driven library services.